PENGGUNAAN ARSIP FILM PROPAGANDA ROMUSHA MASA PENDUDUKAN JEPANG SEBAGAI SUMBER BELAJAR SE-JARAH PESERTA DIDIK - Dio Yulian Sofansyah (Jurnal Pendidikan Sejarah Indonesia, 2021)
With regard to content about the Japanese occupation in history lectures in universities, most of the available material is in textual form, especially in history textbooks. Meanwhile, there is an abundance of archival videos available about this topic that could be used as media or learning materials in classroom learning. This research aims to offer some ideas in using the propaganda films produced during the Japanese occupation as alternative learning material. By doing so, resources learners are expected to realize the teaching and learning process to be varied, fun, easy to understand, able to stimulate imagination, share events that previously abstract in a short time and can bring learners through space and time indirectly because the film media in accordance with the material, needs and objectives proses teaching and learning.